A cross-sectional study to analyze the pattern of pharmacotherapy and its associated factors among patients with schizophrenia - B. S. Abhishree; Shreya Bhat; Sushma Muraraiah; Kavitha Rajarathna (Telangana Journal of Psychiatry)
Background: Schizophrenia, a severe chronic mental disorder, is primarily treated with pharmacotherapy, typically involving either first-generation antipsychotics (FGA) or second-generation antipsychotics (SGA) or a combination of both. The selection of antipsychotics, transitions between medications, and the consideration of combination therapies are influenced by various factors. Aims and Objectives: This study aimed to determine the pattern and factors associated with pharmacotherapy along with adverse drug reactions among patients with schizophrenia. Subjects and Methods: A cross-sectional study with 60 adults diagnosed with schizophrenia and on antipsychotic medications for at least 3 months was conducted. Demographic data, prescription details, and severity of disease were assessed using the Brief Psychiatric Rating Scale. The baseline demographics and clinical characteristics were compared among monotherapy and polytherapy using the Chi-square test. Results: Majority of patients were aged between 18 and 45 years. Monotherapy was prevalent in 70%, with risperidone (42%) and clozapine (6%) being the primary choices. The most commonly used combination antipsychotic therapy in 30% of subjects was found to be risperidone and clozapine. Switchover therapy from FGA to SGA and additional therapy with SGA were observed in 35% and 15% of the study population, respectively. Sociodemographic variables, frequency of hospitalization, or symptomatic episodes did not influence the choice of mono or combination therapy of antipsychotics. Conclusion: Majority of patients were on antipsychotic monotherapy, and the switching of antipsychotics was related to clinical effectiveness and adverse effects. The choice between monotherapy or combination therapy of antipsychotics was not found to be associated with sociodemographic and illness-related variables.